Pathogenetic Mechanisms of the Occurrence of Rheumatoid Arthritis and Ankylosing Spondylitis with the Activation-Enzymatic and Phenotypic Features of Lymphocytes - Lychkovska N.; Chopyak V.; Vorobets Z. (Львівський клінічний вісник)
Introduction. Significant prevalence of inflammatory diseases of the j oints, the tendency to steady increase in their severity, high indicators due to this temporary disability and disability, especially those of middle-aged, determine the important medical and social importance of these diseases. At the present stage, RA and AU are considered as diseases based on immune disorders. It is known that blood lymphocytes are the key cells of the immune system that play a leading role in providing compensatory and adaptive responses of the organism. The variety of visceral manifestations of inflammatory diseases testifies to the participation of universal mechanisms for the implementation of the systemic pathological process involving polypotent messengers with multifunctional effects. These universal messengers include nitrogen oxide (NO), calcium ions Ca2+, which directly or indirectly regulate various physiological and biochemical processes. Studies of biochemistry and physiology in recent decades have shown that precision control (NO) and (Ca2+) and the functioning of cellular enzymatic systems are provided. Among the latter, the leading role in maintaining NO- and ionic homeostasis of the cell belongs to NO synthase, arginase and ATP-bases. However, despite a significant number of studies devoted to the problem of the enzymatic spectrum of lymphocytes, the study of the functional activity of their arginase-NO-synthase and ATP-systems is extremely limited, and the pathophysiological and immune mechanisms of their dysfunction are unclear. The aim of the study. To find out the pathophysiologic mechanisms of the occurrence of rheumatoid arthritis and ankylosing spondylitis with the participation of arginase-NO-synthase and ATP-gidrolase systems of blood lymphocytes and cellular immunity. Materials and methods. The study involved in randomized manner with the preliminary statification the presence of 86 patients, [48 women (56.0 %) and 38 men (44.0 %); aged 18 to 56 years old], who were treated in Lviv Regional Clinical Hospital during 2012-2015. The study involved individuals with a diagnosis of RA or AS without the presence of concomitant lesions of connective tissue of inflammatory nature, other inflammatory diseases, oncological pathology at the time of the beginning of the study. The comparison (control) group consisted of practically (clinically) healthy persons (n = 30), representative by age and gender (57 % women, 43 % men, average age – 37.9 ± 2.2 years). Mononuclear lymphocytes of human peripheral blood were isolated from heparinized freshly-received blood in a density gradient of the ficol triumbras. The viability of lymphocytes, which in all experiments was not less than 95.0 %, was evaluated by the color of trypan blue. In order to permeabilize the blood lymphocyte membranes and to reveal latent enzymatic activity to the suspension of lymphocytes, 0.1-0.3 % saponin was added. Quantitative determination of the populations and subpopulations of lymphocytes was determined by the method of indirect immunofluorescence reaction with monoclonal antibodies to differentiating antigens of cell surface. Determination of phagocytic activity of neutrophils by absorption capacity was carried out on the basis of the method based on endocytosis with phagocytes of latex particles, which digitized cells in the cytoplasm in the form of round granules of blue color. The activity of NO-synthase was determined by the specific cleavage of NADPH(H+). The activity of blood lymphocytes arrhiza was determined by the formation of urea. Ca2+, Mg2+, and Na+, K+ -ATFase activity of blood lymphocytes were determined spectrophotometrically by recording the process of hydrolysis of ATP on the accumulation of Rh. The protein content of the lymphocyte mixture was determined using the modified O. Lowry method. Results. As a result of the conducted studies, changes in the activity of the arginase-NO-synthase system of the lymphocytes of the blood, the violation of the functional activity of the cells of the phagocytic system, and the change in the ratio of T-lymphocyte subpopulations in patients with inflammatory diseases of the joints have been detected. The growth of iNOS activity in these patients is accompanied by compensatory inhibition of the activity of the endothelial isoform NOS. Significant activation of iNOS activity leads to excessive NO formation in blood lymphocytes. NO in high concentrations triggers oxidative and nitrosisic stress, which leads to a disturbance of the antioxidant-antioxidant balance. As a result, activation of apoptotic mechanisms and initiation of destructive processes in the cells occur, leading to an increase in dysfunction. At the same time, inhibition of the activity of ATPase systems indicates an overload of lymphocyte cytosol by Na+ and Ca2+ ions and a violation of ionic homeostasis, which contributes to the occurrence of cellular disturbances. Conclusions. In patients with rheumatoid arthritis, due to the reduced number of T-cytotoxic lymphocytes, the number of T-helper cells, natural killer cells, and regulatory T-lymphocytes, cells with suppressive activation, activated, which indicates the activation of the cellular link of autoagression with the inclusion of regulatory mechanisms, and in patients for ankylosing spondylitis – activation of natural killer cells, activated T-lymphocytes, lymphocytes with suppressive activation and a decrease in the number of regular lymphocytes, indicating an increase in them. More pronounced changes in helper-cytotoxic (CD4+ and CD8+), activated (CD3+/CDHLA-DR+), suppressive (CD4/CD25+) T-lymphocytes and B-lymphocytes (CD19+), regulatory cells (CD4+/CD25+) were verified in patients with rheumatoid arthritis, as compared to patients with ankylosing spondylitis, indicating that there is a more powerful immune-dependent autoagression in patients with rheumatoid arthritis. Violation of the cellular level of immunity is accompanied by suppression of the activity of endothelial NO-synthase of blood lymphocytes in patients with rheumatoid arthritis by 34.9 ± 7.8 % (p < 0,05), in patients with ankylosing spondylitis – by 43.4 ± 6.2 % (p < 0.001) compared to practically healthy subjects with the simultaneous activation of its inducible isoform. The activity of the blood lymphocyte arrhythmias in rheumatoid arthritis patients increases by 178.3 ± 22.3 % (p < 0.001), with ankylosing spondylitis – by 272.6 ± 30.2 % (p < 0.001), compared with practically healthy subjects. NO synthesis was accompanied by suppression of the activity of Ca2+, Mg2+-ATPases of the plasma membrane of blood lymphocytes in patients with RA by 46.8 ± 5.7 % (p < 0.001), in patients with AS – by 39.4 ± 6.4 % (p < 0.001), activity of Ca2+, Mg2+ -ATPase of membranes of EPR of lymphocytes in patients with both pathologies by 35.6 ± 4.8 % (p < 0.001) and 20.0 ± 3.8 % (p < 0.001) respectively. The activity of Na+, K+-ATPase of blood lymphocytes in patients with both pathologies was 42.8 ± 7.2 % (p < 0.001) and 39.7 ± 6.5 % (p < 0.001), respectively, compared with practically healthy subjects. Changes in the activity of arginase-NO-synthase and ATPase system of lymphocytes in patients with rheumatoid arthritis are more pronounced than with ankylosing spondylitis, but the most sensitive parameter is the activity of iNOS, which indicates the crucial role of disorders in this regulatory system for the formation and increase of inflammatory joint damage.